Review Artikel: Evaluasi Efektivitas Perbandingan Preparasi Sampel Pada Instrumen Spektrofotometri Serapan Atom (SSA) Untuk Menganalisis Logam Timbal - Putri, Indah Syah; Damara , Dandy Satria; Akifah , Muthia Nur; Utami , Marsah Rahmawati (Journal of Pharmaceutical and Sciences, 2025)
Lead (Pb) is a hazardous substance that has the potential to damage human health and the environment. This article evaluates the effectiveness of two sample preparation methods, namely wet digestion and dry digestion, in analyzing lead using Atomic Absorption Spectrophotometry (AAS) through a literature review, obtaining data using Google Scholar's “Publish or Perish” feature with the keywords lead, AAS, sample preparation, and method validation. Inclusion criteria are journals published within the last 10 years, while exclusion criteria are  journals that use methods other than AAS, focusing on other metals, or do not involving sample preparation methods involving destruction. The wet destruction method involves dissolving the sample in acid, while the dry destruction method uses high-temperature heating to form dry ash. The dry destruction method demonstrates better analytical performance than wet destruction, based on the parameters of recovery (98.5–104.2%), accuracy (absolute deviation <2%), and precision (%RSD <5%). These results indicate that dry destruction provides more accurate, precise, and consistent analysis, as well as more reliable quantification of elements such as heavy metals, compared to wet destruction, which tends to produce variations between replicates. Therefore, the dry destruction method is recommended for lead analysis using SSA because it is more effective and efficient.